Foraging movements of humpback whales relate to the lateral and vertical distribution of capelin in the Barents Sea - Vogel, Emma F.; Skalmerud, Stine; Biuw, Martin; Blanchet, Marie-Anne; Kleivane, Lars; Skaret, Georg; Øien, Nils; Rikardsen, Audun (Frontiers in Marine Science, 2023)
Understanding how individual animals modulate their behaviour and movement patterns in response to environmental variability plays a central role in behavioural ecology. Marine mammal tracking studies typically use physical environmental characteristics that vary, and/or proxies of prey distribution, to explain predator movements. Studies linking predator movements and the actual distributions of prey are rare. Here we analysed satellite tag data from ten humpback whales in the Barents Sea (north-east Atlantic) to examine how their spatial movement and dive patterns are influenced by the geographic and vertical distribution of capelin, which is a key prey species for humpback whales. We used capelin density estimates based on direct observations from a trawl-acoustic survey and sun elevation to explore the drivers of changes in movement patterns. We found that the humpback whales’ exhibited characteristic area restricted search movement where capelin density was the highest. While horizontal movements showed both positive and negative individual relationships with sun elevation, humpback whale dive depth was positively correlated with diurnal variations in the vertical distribution of capelin. This suggests that in addition to whales foraging in regions of high capelin density, they also target the densest shoals of capelin at a range of depths, throughout the day and night. Overall, our findings suggest that regions of high capelin density are important foraging grounds for humpback whales, highlighting the central role capelin plays in the Barents Sea marine ecosystem.